2011
DOI: 10.1097/rlu.0b013e3181feefe8
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT of Osteitis Condensans Ilii

Abstract: A 16-year-old, nonpregnant, healthy, and sportive teenager suffers from intermittent low back pain. Pelvic x-ray complemented by bone-SPECT/CT demonstrated an uncommon benign condition called osteitis condensans ilii. In the early phase, it is of paramount importance to distinguish osteitis condensans ilii from sacroiliitis or ankylosing spondylitis. This case report highlights the incremental value of performing one-stop shop hybrid SPECT/low-dose CT bone imaging in diagnosing and managing this rare benign sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…[19] Another report explained the use of pelvic X-ray coupled with bone-single PECT (SPECT)/CT to distinguish OCI in the early stages from AS or sacroiliitis. [20] One-stop shop hybrid SPECT/low-dose CT was also advocated as viable alternative. In nutshell, there has been the advent of interesting radiological advances to diagnose or differentiate OCI from other conditions.…”
Section: Diagnosismentioning
confidence: 99%
“…[19] Another report explained the use of pelvic X-ray coupled with bone-single PECT (SPECT)/CT to distinguish OCI in the early stages from AS or sacroiliitis. [20] One-stop shop hybrid SPECT/low-dose CT was also advocated as viable alternative. In nutshell, there has been the advent of interesting radiological advances to diagnose or differentiate OCI from other conditions.…”
Section: Diagnosismentioning
confidence: 99%
“…78 OCI is considered a diagnosis of exclusion because plain radiograph and MRI findings of the spine were unremarkable; 79 while the characteristic X-ray image may show triangular sclerotic changes in the auricular portion of the bilateral ilium with preserved SI joint space. 80,81 Patients mostly exhibit normal physical and neurological examination but some show SI joint region tenderness and increased lumbar lordosis. 59 From a case-control study, OCI is shown to be associated with pain on SI stress tests.…”
Section: Quantitative Sacroiliac Scintigraphy For Osteitis Condensans Iliimentioning
confidence: 99%
“…MRI, SPECT, and PET/ CT might have the ability to distinguish OCI from other diseases and require larger-scale studies before use in the clinical setting. 81,83,84 Quantitative Sacroiliac Scintigraphy for Periostitis-Induced Sacroiliac Pain Juvenile-onset HLA-B27-associated 'unclassifiable' SpA, especially cases without evidence of enteric or genitourinary symptoms, may have tarsal periostitis as an early clinical manifestation and then show bilateral sacroiliac pain later on. 85 One article has reported improvements of the SI joint after convalesce of the foot periostitis, and concluded that stress events, exercise, and abnormal posture can all increase SI ratios, while corrected posture for a period of time, anti-inflammatory drugs, and rehabilitation programmes can all reduce SI ratios.…”
Section: Quantitative Sacroiliac Scintigraphy For Osteitis Condensans Iliimentioning
confidence: 99%